Current State of Knowledge about Autism Spectrum Disorder Based on DSM-5 in the General Population of Faisalabad City, Pakistan: A Survey Study - Hina Hidayat Ali; Muhammad Nazir; Muhammad Naeem Mohsin (JIE, 2025)
The present study expands understanding of public awareness by assessing a current knowledge and awareness levels of general population regarding autism spectrum disorder (ASD) in Faisalabad, Pakistan. Despite increasing global awareness of ASD, limited research has been conducted on the general population’s knowledge of ASD in Faisalabad, Pakistan. Therefore, it was crucial to assess the current state of public knowledge and awareness regarding ASD in Faisalabad, Pakistan. The present study adopted descriptive survey method to answer the research questions. The sample of the study comprising 60 respondents was chosen through convenience sampling technique from public having some affiliations with ASD students. A self-made questionnaire was designed for the data collection from respondents. The results of the study represented that there was a low level of general knowledge about the ASD children among the general population. There was a moderate level of awareness about the social interaction, repetitive behavior and restricted behavior of the ASD children among the general masses. No significant variation in the level of knowledge about the ASD children was noted among the respondents based on their gender, qualification and institutional sector.